Phakomatosis pigmentovascularis cesioflammea associated with focal myoclonic seizures: First case report in Peru - Vences, Miguel A. (2020)
Phacomatosis pigmentovascularis is a rare congenital syndrome, characterized by the simultaneous presentation of a capillary vascular malformation and a cutaneous pigmentary lesion, without or with extracutaneous involvement. The case of an adolescent with epilepsy characterized by focal myoclonic seizures uncontrolled by an irregular pharmacological treatment, with skin lesions compatible with nevus flammeus and dermal, ocular and palatal melanosis since birth, is presented. This is the first report in the country of an infrequent neurocutaneous syndrome and its clinical association with epilepsy, highlighting besides the importance of a comprehensive evaluation of this entity.